2020
DOI: 10.1029/2020sw002501
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Global Ionospheric TEC Using Deep Learning Approach

Abstract: Global ionospheric total electron content (TEC) maps are widely utilized in research regarding ionospheric physics and the associated space weather impacts, so there is a great interest in the community in short‐term ionosphere TEC forecasting. In this study, the long short‐term memory (LSTM) neural network (NN) is applied to forecast the 256 spherical harmonic (SH) coefficients that are traditionally used to construct global ionospheric maps (GIM). Multiple input data, including historical time series of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(77 citation statements)
references
References 30 publications
1
76
0
Order By: Relevance
“…The model results show that the first/second hour TEC root mean square error (RMSE) is 1.27/2.20 TECU during storm time and 0.86/1.51 TECU during quiet time. Comparing with the CODE GIMS, the RMSE of the LSTM prediction is 1.06/1.84 TECU for the 1st /2nd hour, while the RMSE errors from the IRI-2016 and NeQuick-2 models are around 9.21/5.5 TECU, respectively (Liu et al, 2020). Moreover, typical large-scale ionospheric structures, such as equatorial ionization anomaly and storm-enhanced density are well reproduced in the predicted TEC maps during storm time.…”
Section: Total Electron Content (Tec) Mapsmentioning
confidence: 80%
See 1 more Smart Citation
“…The model results show that the first/second hour TEC root mean square error (RMSE) is 1.27/2.20 TECU during storm time and 0.86/1.51 TECU during quiet time. Comparing with the CODE GIMS, the RMSE of the LSTM prediction is 1.06/1.84 TECU for the 1st /2nd hour, while the RMSE errors from the IRI-2016 and NeQuick-2 models are around 9.21/5.5 TECU, respectively (Liu et al, 2020). Moreover, typical large-scale ionospheric structures, such as equatorial ionization anomaly and storm-enhanced density are well reproduced in the predicted TEC maps during storm time.…”
Section: Total Electron Content (Tec) Mapsmentioning
confidence: 80%
“…Spherical harmonic (SH) fitting is often used in constructing the GIM map. We applied an LSTM neural network method (LSTM/NN, Hochreiter and Schmidhuber, 1997) to forecast the 256 SH coefficients, which are then used to construct the GIM maps (Liu et al, 2020). The model results show that the first/second hour TEC root mean square error (RMSE) is 1.27/2.20 TECU during storm time and 0.86/1.51 TECU during quiet time.…”
Section: Total Electron Content (Tec) Mapsmentioning
confidence: 99%
“…Areas of interest go from the core GNSS goal, improving localization (Hosseinyalamdary 2018; Diggelen 2019) to all other bias effect presented in Eq. ( 1) like multipath (Diggelen and Wang 2020; Quan et al 2018), ionosphere (Orus 2018;Jiao et al 2007;Liu et al 2020;Linty et al 2019) and troposphere (Benevides et al 2019) effects. These works demonstrate how ML can contribute to address problems addressed in a different way.…”
Section: Machine Learning For Gnssmentioning
confidence: 99%
“…McGranaghan et al (2017) demonstrated successful application of network analysis to an ionospheric dataset and discovered connections between multi-scale TEC properties and solar influences. Machine learning shows promise in TEC forecasting (Liu et al, 2020). Chen et al (2019) demonstrated a deep learning based approach to fill in missing information in TEC maps.…”
Section: Introductionmentioning
confidence: 99%